Lifelines for the isolated : the supply, training and professional support of educational personnel in multi-island situations - Weeks, John (Commonwealth Secretariat LondonGB, 1994)
Examines the personal situation of those who serve education in remote locations. Seeks ways of providing strategies to meet their professional needs. Presents two case studies.